An Integrative Model of Local Wisdom-Based Learning at Pesantren: A Comparative Study of Islamic Educational Institutions in Indonesia - Susanto, Roni; Syahrudin; Ummah, Wardatul; Musyafa’, A’ang Yusril; Isa, Khairunesa (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study aims to investigate an integrative innovation model to bridge the weak integration of local wisdom curriculum in Islamic boarding school education. This study used a qualitative method with an ethnographic approach. This research was conducted in five Islamic boarding schools: Walisongo Islamic boarding school in Lampung, Al-Kayyis Islamic boarding school in Banten, Al-Mahalli Islamic boarding school in Yogyakarta, Al-Hasan Islamic boarding school in Ponorogo, and Darul Hikam Bendo Islamic boarding school in Kediri. The forms of local wisdom in Islamic boarding schools include gotong royong, piil pesegiri, agrarian culture, social ethics, and digital creativity. Data analysis employed the Folk Development Analysis (FDA), which involved identifying elements of local wisdom, internalization processes, and interpretations. The results of the study show that those five Islamic boarding schools have succeeded in integrating local wisdom values ​​through three main pillars: (1) strengthening local values ​​through the Islamic boarding school curriculum, (2) a socially based contextual approach in the culture of students, and (3) methodological innovations that are in accordance with developments in the digital era. The form of implication of the integration of these values ​​is the formation of a strong, relevant, and adaptive character of students in preserving local wisdom.